Comparing democracies 4 elections and voting in a changing world - LeDuc, Lawrence; Niemi, Richard G.; Norris, Pippa (Sage Publications, 2014)
Changes since the last edition: * The previous edition didn't quite fit modules on either comparative politics or voters and elections. The new edition is more closely mapped to modules on the latter. * New chapters on authoritarian elections and regime change, and electoral integrity. * Re-inclusion of a chapter on voting behaviour. * Stronger focus on the economy
Keywords: Democracy; Comparative government